Kealpaan Yang Berakibat Luka Berat Dan Kematian Pada Sebuah Pertandingan Olahraga - Rizky Maulana Hakim (Jurist-Diction, 2024)
Sports in an activity that every human being does every day around the world. Regarding sports themselves, such as heavy sports, suach as for example football and boxing, where in the two sports that have been mentioned these are heavy sports, which in these heavy sports violations will often occur, whether these violations are commited by the athletes themselves, or commited by between athletes with a specific purpose. In this case it discusses the definitions of football and boxing matches, the procedures in both sports and what if in both sports an accident occurs causing serious injury or even death. Using two research methods, namely the concept approach (Conceptual Approach), and using the Statutory Approach (Statute Approach), namely by referring to the laws that are generally enforced and specific law that regulate related to the existing rules in these two sports, namely football and boxing.